2013
DOI: 10.1038/srep02566
|View full text |Cite
|
Sign up to set email alerts
|

Realization of ferromagnetic graphene oxide with high magnetization by doping graphene oxide with nitrogen

Abstract: The long spin diffusion length makes graphene very attractive for novel spintronic devices, and thus has triggered a quest for integrating the charge and spin degrees of freedom. However, ideal graphene is intrinsic non-magnetic, due to a delocalized π bonding network. Therefore, synthesis of ferromagnetic graphene or its derivatives with high magnetization is urgent due to both fundamental and technological importance. Here we report that N-doping can be an effective route to obtain a very high magnetization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 50 publications
(76 reference statements)
3
72
0
1
Order By: Relevance
“…46 The * resonance peak at 397.7 eV, attributed to pyridine-like bonding, arises due to transitions from the K-shell (N 1s) to the unoccupied * orbital. 48,49 The peak position of the pyridine like species is however 1.0 eV lower to that reported by Liu et al in the case of nitrogen doped graphene oxide 21,47 and that by Usachov et al in their study of N-graphene synthesised from s-triazine molecules. 44 Comparing the deconvoluted N K-edge spectra of the N-functionalised samples (Figs 2(c, d)), the most significant difference observed is the peak III (attributed to pyrrolic nitrogen), thus indicating higher pyrrolelike bonding for FLG:N (PECVD) samples.…”
Section: 39mentioning
confidence: 44%
See 4 more Smart Citations
“…46 The * resonance peak at 397.7 eV, attributed to pyridine-like bonding, arises due to transitions from the K-shell (N 1s) to the unoccupied * orbital. 48,49 The peak position of the pyridine like species is however 1.0 eV lower to that reported by Liu et al in the case of nitrogen doped graphene oxide 21,47 and that by Usachov et al in their study of N-graphene synthesised from s-triazine molecules. 44 Comparing the deconvoluted N K-edge spectra of the N-functionalised samples (Figs 2(c, d)), the most significant difference observed is the peak III (attributed to pyrrolic nitrogen), thus indicating higher pyrrolelike bonding for FLG:N (PECVD) samples.…”
Section: 39mentioning
confidence: 44%
“…Indeed, Liu et al 21 have observed high values of magnetization in ferromagnetic graphene oxide (GO), when doped with nitrogen. The substitution by nitrogen of a carbon atom in the graphene lattice leads to an increase in the electronic density of states and the nitrogen dopant can provide -electron close to the Fermi level of graphene, thereby enhancing the coupling via a reduction in the magnetic moment distance.…”
Section: -19mentioning
confidence: 99%
See 3 more Smart Citations